Cyclic codes from Whiteman's generalized cyclotomic sequences of order 2r, r ≥ 2. Issue 3 (19th May 2017) - Pankaj,; Pruthi, Manju
Abstract: In this paper, the two-prime Whiteman's generalized cyclotomic sequences of order 2 r, r ≥ 2, are employed to construct several classes of cyclic codes over the finite field GF ( q ) with length n 1 n 2 . The lower bounds of the minimum distance of these cyclic codes are obtained.